2008
DOI: 10.1158/0008-5472.can-07-5582
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Yin Yang 1 Protein in Osteosarcoma Cells on Cell Invasion and CXCR4/Angiogenesis and Metastasis

Abstract: We know that the Yin Yang 1 protein (YY1) overexpression is positively and strongly correlated with the degree of malignancy of bone tumors. Therefore, we questioned whether we could influence cell invasiveness by deleting YY1 in human osteosarcoma cells (SaOs-2), as tested in Matrigel-coated filters and metastasis implantation of such osteosarcoma cells in vivo, by serial analysis with nuclear magnetic resonance. Moreover, we focused our work on the chemokine receptor CXCR4 and its inhibition by T22 antibody,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 35 publications
5
83
0
Order By: Relevance
“…While, Kijowski et al 35 demonstrated the stimulation of VEGF secretion by SDF-1-CXCR4 axis, using human hematopoietic cell lines. Because then, a close correlation between CXCR4 and VEGF expression has been demonstrated in epithelial malignancies 12,13 and osteosarcoma, 36 both in vitro and in vivo. In our previous study, we found a significant positive correlation between immunohistochemical VEGF and CXCR4 expression.…”
Section: Discussionmentioning
confidence: 97%
“…While, Kijowski et al 35 demonstrated the stimulation of VEGF secretion by SDF-1-CXCR4 axis, using human hematopoietic cell lines. Because then, a close correlation between CXCR4 and VEGF expression has been demonstrated in epithelial malignancies 12,13 and osteosarcoma, 36 both in vitro and in vivo. In our previous study, we found a significant positive correlation between immunohistochemical VEGF and CXCR4 expression.…”
Section: Discussionmentioning
confidence: 97%
“…The search site predicted a series of transcription factors that might be involved in the transcriptional regulation of let-7a (Table 1). The transcription factor Yin Yang 1 (YY1), ranked first in the prediction, is a member of the polycomb group and has been shown to be involved in CXCR4 signaling (25)(26)(27)(28)(29).…”
Section: Figurementioning
confidence: 99%
“…Genetic mutations and polymorphisms, which provide predisposition to the onset of osteosarcoma and affect survival, were also taken into account (25,26,27). Other genetic studies concern the mechanisms of resistance to cisplatin (28), doxorubicin and methotrexate (29).…”
Section: Bone Tumoursmentioning
confidence: 99%